Promoting Students’ Critical Thinking Skill Through Stem-Based Learning on Trigonometry - Lestiana, Herani Tri; Toheri, Toheri; Nur'aeni, Sri (Al-Khawarizmi, 2022)
This study aims to promote students' critical thinking skills of trigonometry by using STEM-based learning. This study was an experimental study conducted on 10th grade students of social studies MAN 1 Cirebon. The data were collected by using tests. The result showed that there was an improvement of students’ critical thinking skills after the implementation of STEM-based learning on trigonometry. Students’ posttest score of 79.83 was greater than the pretest score, which was 30.81. The paired sample t-test analysis showed that there was a significant increase from pretest to posttest score. Thus, it can be concluded that there STEM-based learning can be applied to promote students' critical thinking skills.